2014
DOI: 10.3389/fncel.2014.00097
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms of immunomodulation in the brain through environmental enrichment

Abstract: Recent studies on environmental enrichment (EE) have shown cytokines, cellular immune components [e.g., T lymphocytes, natural killer (NK) cells], and glial cells in causal relationship to EE in bringing out changes to neurobiology and behavior. The purpose of this review is to evaluate these neuroimmune mechanisms associated with neurobiological and behavioral changes in response to different EE methods. We systematically reviewed common research databases. After applying all inclusion and exclusion criteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(89 citation statements)
references
References 323 publications
1
82
1
Order By: Relevance
“…There is a plethora of evidence supporting the benefits of enrichment for animals held in captivity, particularly mammals (Simpson and Kelly, 2011;Singhal et al, 2014). However, evidence for the benefits or otherwise of enriched environments for fish is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a plethora of evidence supporting the benefits of enrichment for animals held in captivity, particularly mammals (Simpson and Kelly, 2011;Singhal et al, 2014). However, evidence for the benefits or otherwise of enriched environments for fish is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory rodent studies, enrichment can improve the health and welfare of the test subjects but may also reduce individual variation such that the data sets are more robust and scientifically valid (Singhal et al, 2014). The present study was conducted to investigate the effects of simple environmental enrichment on (i) the recovery of rainbow trout from stressors and invasive procedures, and (ii) the degree of interindividual variability among the data collected.…”
Section: Introductionmentioning
confidence: 99%
“…EE causes a significant change in the genetic expression of genes that are involved in neuronal structure, plasticity, and neurotransmission [12]. Furthermore, EE can affect cytokine production and glial cell function [13]. Taken together, evidence indicates that EE can modulate brain function by improving learning and memory and reducing memory loss in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…listening to music), have shown that EE improves cognition and memory. [20] Although more work is required, this study suggests that similar non-pharmacological approaches may be relevant to treat depression associated with stress and diabetes.…”
Section: Spotlight On Original Articlesenvironmental Enrichment Limitmentioning
confidence: 89%